2014
DOI: 10.1186/1476-4598-13-128
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein accelerates hepatocarcinogenesis with partner survivin through modulating miR-520b and HBXIP

Abstract: BackgroundHepatitis B virus X protein (HBx) plays crucial roles in hepatocarcinogenesis. However, the underlying mechanism remains elusive. We have reported that HBx is able to up-regulate survivin in hepatocellular carcinoma tissues. The oncopreotein hepatitis B X-interacting protein (HBXIP), a target of miR-520b, is involved in the development of cancer. In this study, we focus on the investigation of hepatocarcinogenesis mediated by HBx.MethodsThe expression of HBx and survivin was examined in the liver tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
0
43
0
1
Order By: Relevance
“…For example, HBV mRNA can reduce the level of miR-122 by direct absorption to promote hepatocellular carcinoma tumor growth (11), and the HBx protein modulates the tumor suppressor miR-520b, accelerates hepatocarcinogenesis, and represses miR-148a to inhibit the AKT/ ERK/FOXO4/ATF5 pathway (9,36). It has been reported that miR-15a plays important roles in apoptosis, cell proliferation, and tumorigenesis by targeting different mRNAs in various cancers (13,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HBV mRNA can reduce the level of miR-122 by direct absorption to promote hepatocellular carcinoma tumor growth (11), and the HBx protein modulates the tumor suppressor miR-520b, accelerates hepatocarcinogenesis, and represses miR-148a to inhibit the AKT/ ERK/FOXO4/ATF5 pathway (9,36). It has been reported that miR-15a plays important roles in apoptosis, cell proliferation, and tumorigenesis by targeting different mRNAs in various cancers (13,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Positive cells were scored as follows: ,10% as negative, "-"; 3%-10% as low expression, "+"; 30%-50% as moderate expression, "2+"; positive cells .50% as strong expression, "3+"; the latter three categories represent positive expression of marker proteins. 21 …”
Section: Immunohistochemistry Analysismentioning
confidence: 99%
“…According to the results, the remarkably reduced miR‐520e was observed in Huh7‐X and HepG2‐X cells, but it presented a significant increase in a dose‐dependent manner in Huh7‐X, HepG2‐X and HepG2.2.15 cells after interfering HBx, which indirectly confirmed that HBx could downregulate the expression of miR‐520e. Interestingly, Zhang et al also reported that HBx can reduce the expression of miR‐520b, a member of miR‐520 family, by forming complex with transcription factor Sp‐1 and survivin in liver cells, which also provided the possibility that the downregulation of miR‐520e in HBV‐positive HCC cells may result from the inactivation of miR‐520e promoter caused by the interaction between HBx and Sp‐1.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there was evidence indicated that miR‐520 family, served as anti‐onco‐miRNAs, was implicated in regulating the tumorigenesis and development of various solid cancers . To be specific, miR‐520b, as a member of miR‐520 family, was reduced, while its target gene ( HBXIP ) was elevated, both of which were mediated by HBx, contributing to hepatocarcinogenesis in vitro and in vivo . Of note, as another member of miR‐520 family, miR‐520e was also reported able to target NF‐kappaB‐inducing kinase (NIK) to mediate NIK/phosphorylated extracellular signal‐regulated kinase 1/2 (p‐ERK1/2)/Nuclear factor kappa‐B (NF‐κB) pathway, and thereby inducing the occurrence of HCC .…”
Section: Introductionmentioning
confidence: 99%